Output-Based Aid in Mongolia : Expanding Telecommunications Services to Rural Areas - Dymond, Andrew; Oestmann, Sonja; McConnell, Scott (World Bank, Washington, DC, 2012)
Access to telecommunications services has been extremely limited in the remote and sparsely populated areas of Mongolia. Several factors have conspired against achieving universal access on a purely commercial basis the country's vast and challenging geography, the nomadic lifestyle of the rural population, government ownership and incumbent control of the long-distance transmission network. As first steps in rolling out a universal access program, two pilot projects are bringing phone service to remote herder communities and both mobile phone and Internet services to rural villages. To support the delivery of these services, onetime subsidies were competitively awarded to licensed telecommunications operators in Mongolia. These are output-based subsidies: the winning bidders take on the investment risks of expanding their networks, receiving subsidy payments largely only after meeting service targets. The operators are obligated to continue offering the services for the duration of their 5 year service agreements without further subsidy.